Natural Lighting Study of the Smith Alam Sutra Building, Tangerang City - Hendro Wahyu Purwanto; Samsu Hendra Siwi; Eddy Supriyatna Marizar (Fakultas Teknik Universitas Pancasila, 2024)
In architectural planning, natural lighting systems need to be considered. With the right program, natural light has an impact on occupant productivity and satisfaction. Controlling lighting use is necessary to manage the glare effect in the room, in addition to its advantages in terms of energy efficiency. The application of minimalist facade systems without additional shading elements is increasing in number, and the form is increasingly minimalist. Minimalist facade designs are not suitable for use in tropical countries with abundant sunlight. Apart from increasing the cost of electrical loads, sunlight penetrating buildings through transparent walls or glass also causes a glare effect in space. Therefore, it is necessary to study and implement the lighting system correctly to ensure a high-quality room atmosphere. The research method uses a mixed-methods approach, carried out using an explanatory sequential strategy. The analysis process begins with a qualitative research stage, followed by quantitative research. Research data was obtained from literature studies, observations, and interviews with planners, owners, and residents. The simulation results showed that the installation of shading (horizontal, vertical, and combined) on the west side, following the SNI no. 03-2396-2001 method to reduce glare, did not decrease the value of light exposure received by the building mass of the Smith building. Based on the activities conducted, measurements on units that are already operational, and which are still in standard condition have informed us that proper interior implementation contributes to decreasing light intensity values in office, SOHO, and apartment spaces